Pengaruh Metode Pembelajaran Latihan Terbimbing Terhadap Motivasi dan Hasil Belajar Matematika Siswa Kelas XI Fase F SMA Negeri 1 Candung Agam - Rahmadani, Desi; Aniswita, Aniswita; Rusdi, Rusdi; Risnawita, Risnawita (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to examine the effect of the Directed Practice learning approach on the motivation and learning outcomes of mathematics students in grade XI Phase F at State High School 1 Candung for the 2023/2024 academic year. The method used is pre-experimental with a Static Group Comparison design. The research sample consists of 54 students selected through random sampling techniques from a population of 79 students. The XI Phase F3 class is designated as the experimental group that receives instruction with the Directed Practice approach, while the XI Phase F2 class serves as the control group that receives conventional instruction. The instruments used in this study include learning outcome tests and motivation questionnaires. Data analysis was performed using the t-test with the help of SPSS software. The results of the analysis show that there is a significant difference between the experimental group and the control group, both in terms of learning motivation and mathematics learning outcomes. For learning motivation, a calculated t-value of 3.1656 was obtained > table t = 1.63756 with a significance value of 0.003 < 0.05. Meanwhile, for mathematics learning outcomes, a calculated t-value of 2.234 was obtained > table t = 1.63756 with a significance value of 0.03 < 0.05. Thus, it can be concluded that the Directed Practice learning approach has a significant effect on improving the motivation and mathematics learning outcomes of the XI Fase F students at SMA Negeri 1 Candung